A STUDY ON ENTREPRENEURSHIP IN SMALL TEA PLANTATIONS WITH SPECIAL REFERENCE TO ASSAM - Kakati, Tapan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Entrepreneurship in small tea plantations has reshaped Assam’s rural economy over the past three decades. This paper examines how small tea growers (STGs)—holdings up to 10.12 hectares—mobilize land, labor, and local networks to create self-employment and enterprise opportunities. Using secondary sources up to 2022 (Tea Board of India, Economic Survey of Assam/NEDFi, NABARD district studies, and peer-reviewed work), we analyze sectoral scale, organization, pricing, credit, and capability gaps, situate Assam within national production patterns, and discuss gendered employment effects and climate exposure. Descriptive statistics and value-chain analysis show that (i) STGs nationally contributed roughly half of India’s tea output in 2019; (ii) Assam remained a cornerstone producer with 2018–2021 production ranging ~619–716 million kg; and (iii) entrepreneurial returns hinge on green-leaf price realization, quality compliance, access to finance, and buyer linkages with bought-leaf factories (BLFs). The paper recommends transparent price discovery, collective action via producer companies, inclusive finance aligned to tea husbandry cycles, quality upgrading, and climate-smart field practices to strengthen smallholder entrepreneurship.